Assessing seasonal and weather effects on depression and physical activity using mobile health data - Yuezhou Zhang; Amos A. Folarin; Yatharth Ranjan; Nicholas Cummins; Zulqarnain Rashid; Pauline Conde; Callum Stewart; Shaoxiong Sun; Srinivasan Vairavan; Faith Matcham; Carolin Oetzmann; Sara Siddi; et al. (npj Mental Health Research)
Abstract Seasonal and weather changes can significantly impact depression severity, yet findings remain inconsistent across populations. This study explored depression variations across the seasons and the interplays between weather changes, physical activity, and depression severity among 428 participants in a real-world longitudinal mobile health study. Clustering analysis identified four participant subgroups with distinct patterns of depression severity variations in 1 year. While one subgroup showed stable depression levels throughout the year, others peaked at various seasons. The subgroup with stable depression had older participants with lower baseline depression severity. Mediation analysis revealed temperature and day length significantly influenced depression severity, which in turn impacted physical activity levels indirectly. Notably, these indirect influences manifested differently or even oppositely across participants with varying responses to weather. These findings support the hypothesis of heterogeneity in individuals’ seasonal depression variations and responses to weather, underscoring the necessity for personalized approaches in depression management and treatment.